RETRACTED: Postulation of the Effect of Unpredicted Predisposing Factors for Post-Tonsillectomy Bleeding - Khaled, Mohamed Bofares (Journal of Otolaryngology Advances, 2021)
This article has been retracted on 20 January 2022. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2379-8572.joa-25-5850) Back ground and Objectives Tonsillectomy is the most common surgical procedure in specialty of otorhinolaryngology. Therefore there are frequent premises regarding this procedure to be improved from different aspects, indications, time of surgery, techniques, safety measures, and postoperative care. Hence the tonsils and peritonsillar tissues are highly vascular zone that supplied by direct branches of external carotid artery thus the post-tonsillectomy bleeding remains one of significant issues in relation to this widely performed procedure. The post-tonsillectomy bleeding needs frequently to be postulated for its incidence, prevalence, etiology, predisposing factors, management and prevention. This subject constitutes one of most risky aspects that increase wariness of the surgeons regarding this commonly conducted procedure. Although there are huge numbers of presentative literatures coming from American as well as western institutes that tried to put guidelines for purpose of prevention and management of post-tonsillectomy bleeding but broadly at our middle-east region and locally at our Libyan society we found for some extent difficulties to apply all these guidelines. For this reason this issue has been take the wider spectrum of ENT surgeons’ concentration, discussions, and researches. Therefore this study was conducted prospectively and for long time to confirm the possible predisposing factors that could be responsible for increasing the risk of post-tonsillectomy bleeding at our region and in the same time to illustrate the concluded recommendations to prevent the occurrence of this important complication. Patients and Methods 2880 patients aged from 8 months to 85 years presented at ENT department-AL-hawari ENT and urology teaching center- Benghazi-city – Libya as well as AL-thowra central teaching hospital and AL-tarahom private center – Elbyda city – Libya at period in between September 2003 to March 2015 as cases of chronic adeno-tonsillitis and solitary acute as well as chronic related palatine tonsillar disease with variable patterns of indications for tonsillectomy namely snoring and apnea attacks, recurrent attacks of acute tonsillitis, persistent otitis media with effusion, recurrent attacks of acute suppurative otitis media, failure to thrive, recurrent attacks of chest infection, mal-occlusive dental deformity, unilateral enlarged tonsils, post-traumatic avulsed tonsils, history of quinsy abscess and persistent halitosis. All patients were assessed intra-operatively and post-operatively too for any evidences of primary, reactionary, or secondary hemorrhage in relation to wide spectrum of factors as patient's demographic, medical, and socio-habitual factors, in addition to technical as well as post-operative care factors. Results This presenting study confirmed that the most common type of post-tonsillectomy bleeding was the secondary variety (71%) as compared to primary (22%) and reactionary (7%) among all presented post-tonsillectomy bleeding cases. Although through this presenting serial study there were multifactorial pre-dispositions elucidated for secondary post-tonsillectomy hemorrhage but as general poor post-operative care can be considered as the cornerstone for the pathogenesis of this significantly raised incidence of secondary post-tonsillectomy bleeding this may be in form of inadequate patient's hydration and nutritional supply (47%), poor patient's antibiotic compliance (23%), and child's maternal negligence (19%). The time of surgery was found to be another important pre-disposing factor for post-tonsillectomy bleeding, it was postulated that the incidence of reactionary as well as secondary post-tonsillectomy hemorrhage significantly increased at summer and autumn seasons (69%) as compared to other seasons. The place of surgery was another interesting proposed studied factor among this serial presentation it was observed that the incidence of post-tonsillectomy bleeding among patients who operated at AL-hawari ENT and urology teaching center-Benghazi-city significantly higher (63%) than that among cases who interfered at AL-thowra central teaching hospital and AL-tarahom private center – Elbyda city. Conclusion Generally speaking, post-tonsillectomy bleeding is considered as one of important issues in ENT and one of significant post-tonsillectomy complications which may create a critical morbidity that may rarely extend to post-operative mortality. Hence the most common pattern of post-tonsillectomy bleeding is the secondary type; however this type of post-tonsillectomy hemorrhage is pre-disposed and induced by many factors. Most of these factors are treatable and curable thus the prophylaxis against this significant complication can be achievable.
Keywords: post-tonsillectomy morbidity and mortality; post-tonsillectomy complications; post-tonsillectomy hemorrhage; post-tonsillectomy bleeding.